Transforming Common Service Centers Into Village Knowledge Centers For Effective Delivery Of Agricultural Extension Services To Farmers - Gujji Bhaskar (Journal of Agricultural Extension Management, 2026)
The policy paper explores the potential of transforming Common Service Centers (CSCs) into Village Knowledge Centers (VKCs) to address critical agricultural challenges faced by rural farmers in India. The CSCs, established under National E-Governance Plan (NeGP), currently serve as digital hubs providing government to-citizen (G2C) services, including financial transactions, e-governance, and limited agricultural services. However, with over 596,000 operational CSCs (4.67 lakhs at Gram Panchayats), there remains significant untapped potential to expand their role in rural agricultural empowerment. By transitioning CSCs into VKCs, these centers can deliver tailored agricultural extension services such as crop advisory, soil testing, pest management, and real-time market linkages, directly contributing to the socio-economic development of rural communities. The study identifies several barriers that limit the effectiveness of CSCs in agricultural service delivery. These include a lack of specialized agricultural training for Village Level Entrepreneurs (VLEs), insufficient infrastructure such as internet connectivity and digital tools, and low awareness among farmers about existing CSC services. Farmers report moderate satisfaction with services like government scheme applications but express dissatisfaction with agricultural advisories, citing them as untimely and inadequate. Additionally, financial constraints and limited access to real-time market and price information remain significant challenges for small and marginal farmers. To address these issues, the policy brief proposes a comprehensive roadmap for transforming CSCs into VKCs. Key recommendations include expanding agricultural services to cover agriculture, horticulture, livestock, and fisheries, strengthening VLE capacity through targeted training programs, efficient market linkages, upgrading infrastructure to support advanced tools like soil testing kits and IoT devices and leveraging digital platforms for precision agriculture. These measures aim to make VKCs a one-stop solution for farmers, providing them with the knowledge, tools, and The paper presented the VKC model, the key inputs will enhance the performance of VKCs for the benefit of farming community. The VKC model operates on a clear Theory of Change that links assumptions, inputs, activities, outputs, and outcomes. It assumes that farmers are willing to adopt VKC services if they are accessible, relevant, and affordable, and that VLEs can be trained to deliver high-quality services. The paper also presents an implementation plan for short-term, medium-term and long-term for effective operationalisation of VKCs for effective delivery of agricultural services to farmers in rural India